Immunotherapy plus chemotherapy versus chemotherapy alone in the first-line treatment for advanced gastric cancer/gastroesophageal junction cancer: a real-world retrospective study - Xu, Qian; Yi, Dan; Jia, Caiyan (Frontiers in Immunology, 2024)
BackgroundImmunotherapy offers new hope for improved survival in patients with advanced gastric cancer. Although large randomized controlled trials (RCTs) have been conducted to explore the efficacy and safety of first-line immunotherapy plus chemotherapy versus chemotherapy alone for advanced gastric cancer, the results are not completely consistent. And the strict inclusion criteria of RCTs lead to limited extrapolation. Therefore, it is of great significance to continue to conduct real-world studies comparing the clinical efficacy and safety of immunotherapy combined with chemotherapy versus chemotherapy alone in advanced gastric cancer.MethodsThis retrospective study included patients with HER-2 negative, unresectable advanced or recurrent gastric/gastroesophageal junction cancer (GC/GEJC) who received first-line immune checkpoint inhibitors (ICIs) in combination with chemotherapy or chemotherapy alone between January 1, 2018 to May 31, 2023. Progression-free survival (PFS), overall survival (OS), overall response rate (ORR), disease control rate (DCR) and adverse events (AEs) were compared between two groups.ResultsA total of 210 patients were enrolled in the combination treatment group (n=100) and chemotherapy alone group (n=110). After 12 months of follow-up, median PFS (mPFS) was 270 days (95%CI 177.510-362.490) in the chemotherapy alone group and 357 days (95%CI 250.103-463.897) in the combination treatment group (P<0.05). The median OS (mOS) was 14.9 months (95%CI 9.831-17.769) in the chemotherapy alone group and 15 months (95%CI 12.386-17.614) in the combination treatment group (P>0.05). There was no statistically significant difference in ORR between two groups (P=0.050). The DCR was 14.5% in the chemotherapy alone group and 38% in the combination treatment group (P<0.05). Subgroup analyses showed that primary tumor location of GEJC, ECOG PS of 1, without liver metastasis, and chemotherapy plus ICIs were associated with PFS benefit. Cox multivariate analysis showed that only surgery or not was correlated with patients’ prognosis (P<0.05). Most of AEs were grade 1-2 and manageable.ConclusionsCompared with chemotherapy alone, first-line ICIs combined with chemotherapy in patients with advanced GC/GEJC could greatly prolong PFS, but OS was not significantly improved, and the AEs were manageable.